Evidence for tuning adipocytes ICER levels for obesity care - Brajkovic, Saška; Marenzoni, Raphael; Favre, Dimitri; Guérardel, Audrey; Salvi, Roberto; Beeler, Nicole; Froguel, Philippe; Vollenweider, Peter; Waeber, Gérard; Abderrahmani, Amar (Adipocyte, 2012)
Abnormal adipokine production, along with defective uptake and metabolism of glucose within adipocytes, contributes to insulin resistance and altered glucose homeostasis. Recent research has highlighted one of the mechanisms that accounts for impaired production of adiponectin (ADIPOQ) and adipocyte glucose uptake in obesity. In adipocytes of human obese subjects and mice fed with a high fat diet, the level of the inducible cAMP early repressor (ICER) is diminished. Reduction of ICER elevates the cAMP response element binding protein (CREB) activity, which in turn increases the repressor activating transcription factor 3. In fine, the cascade triggers reduction in the ADIPOQ and GLUT4 levels, which ultimately hampers insulin-mediated glucose uptake. The c-Jun N-terminal kinase (JNK) interacting-protein 1, also called islet brain 1 (IB1), is a target of CREB/ICER that promotes JNK-mediated insulin resistance in adipocytes. A rise in IB1 and c-Jun levels accompanies the drop of ICER in white adipose tissues of obese mice when compared with mice fed with a chow diet. Other than the expression of ADIPOQ and glucose transport, decline in ICER expression might impact insulin signaling. Impairment of ICER is a critical issue that will need major consideration in future therapeutic purposes.